Features of helium complexes behaviour near the free surface in tungsten - Starchenko, I.V.; Sadanov, E.V. (Вопросы атомной науки и техники, 2019)
The formation of interstitial atoms by lattice tungsten atoms displacement by clusters of implanted helium, which is accompanied with the appearance of helium-vacancy complexes, was found. The stimulating effect of the free surface on the development of the processes of displacement and dissociation of complexes has been revealed. It is shown that this influence is caused by the action of image forces. The depth of the image forces was determined, which was about 2.5 nm. Виявлено формування міжвузельних атомів шляхом витіснення граткових атомів вольфраму кластерами імплантованого гелію, яке супроводжується появою гелій-вакансійних комплексів. Виявлено стимулюючий вплив вільної поверхні на розвиток процесів витіснення і дисоціації комплексів. Показано, що цей вплив викликано дією сил зображення. Визначена глибина дії сил зображення, що склала близько 2,5 нм. Обнаружено образование межузельных атомов путем вытеснения решеточных атомов вольфрама кластерами имплантированного гелия, которое сопровождается появлением гелий-вакaнсионных комплексов. Выявлено стимулирующее влияние свободной поверхности на развитие процессов вытеснения и диссоциации комплексов. Показано, что это влияние вызвано действием сил изображения. Определена глубина действия сил изображения, которая составила около 2,5 нм.